2022
DOI: 10.3389/fevo.2022.932344
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuroecology and multimodal evolution across the genus Drosophila

Abstract: The neural basis and genetic mechanisms for sensory evolution are increasingly being explored in depth across many closely related members of the Drosophila genus. This has, in part, been achieved due to the immense efforts toward adapting gene-editing technologies for additional, non-model species. Studies targeting both peripheral sensory variations, as well as interspecies divergence in coding or neural connectivity, have generated numerous, tangible examples of how and where the evolution of sensory-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 154 publications
1
0
0
Order By: Relevance
“…melanogaster is able to detect wavelengths of red light [71]. In support of our finding electroretinographic recordings from stable flies showed strong peaks of visual sensitivities occurring around 605-635 nm, which is red color zone and at UV zone [72,73].This may necessitate to make some adjustment in our future behavioral experiments that uses red light to simulate darkness [74]. Other researchers also demonstrated the wide color preference of stable flies, for instance [75] demonstrated that white coroplast, and even gray ones, were more attractive to Stomoxys than blue coroplasts.…”
Section: Discussionsupporting
confidence: 77%
“…melanogaster is able to detect wavelengths of red light [71]. In support of our finding electroretinographic recordings from stable flies showed strong peaks of visual sensitivities occurring around 605-635 nm, which is red color zone and at UV zone [72,73].This may necessitate to make some adjustment in our future behavioral experiments that uses red light to simulate darkness [74]. Other researchers also demonstrated the wide color preference of stable flies, for instance [75] demonstrated that white coroplast, and even gray ones, were more attractive to Stomoxys than blue coroplasts.…”
Section: Discussionsupporting
confidence: 77%